Análise de exercícios de compreensão de textos em livros didáticos de língua portuguesa para o 6º ano - Custódio, Lívia Cárnio (2015)
The interpretation and understanding of texts are common subjects in teachers' room; the difficulty of the students to understand what they read is commented by teachers in different school subjects. In the case of the Portuguese language teaching, it has been found that a big problem is how the understanding of the texts for the Elementary School is explored in textbooks. There is evidence that the difficulty of the students to understand texts can be linked to the way the textbooks propose work with these activities and implementation that teachers do what is proposed in the didactic material. This research becomes relevant and justified by the need to reflect on approach to exercise reading comprehension of the Portuguese Language, supporting the notion of language as a dialogic and interactive activity and the notion of understanding as an activity and constructive process when it comes to understanding the proposals present in textbooks. Therefore, sought support in Linguistics Textual, especially in Koch's studies (2009; 2012) and Marcuschi (2008) on reading comprehension. This research aims to investigate the exercises of reading comprehension in two Portuguese textbooks used in the 6th year of Elementary School. As corpus were selected the textbooks: Diálogo - Eliana Santos Beltrão and Tereza Gordilo and Vontade de Saber Português - Rosemeire Alves and Tatiane Brugnerotto. For construction of the methodology, this research considered its theoretical and investigative character and identified two analytical steps. The first was on the discussions of the theory proposed for this research. The second step is the analysis of the exercises proposed by the two textbooks that constitutes the corpus of this research. This research is intended to enable reflections on the proposals of understanding in textbooks and how is happening the development of comprehension skills in students.